Unlocking Economic Potential: Financial and Governance Drivers of Firm Value in Indonesia’s Food and Beverage Sector - Yahya, Putri Aleyda; Priharta, Andry (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG), capital structure, and profitability on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. In conditions of increasingly tight business competition, company value is an important indicator that reflects the company's performance and prospects, and attracts investor interest. This study uses a quantitative method with secondary data obtained from the annual reports of manufacturing companies on the IDX. The independent variables used are GCG, capital structure as measured by the Debt to Equity Ratio (DER), and profitability as measured by Return on Assets (ROA). The dependent variable is company value as measured using Price to Book Value (PBV). The results of the study show that GCG, capital structure, and profitability have a significant effect on company value, both partially and simultaneously. Good GCG implementation and optimal capital structure and profitability have been proven to be able to increase company value, which ultimately has a positive impact on investor confidence.